Exploring Translingual Practices as a Pathway to Inclusive Language Acquisition - Kadek Agus Dwi Artha (LIER: Language Inquiry & Exploration Review, 2024)
Purpose: This study explores the role of translingual practices as a pathway to inclusive language acquisition, focusing on how the use of multiple languages in the classroom enhances language learning, engagement, and inclusivity for multilingual students. Subjects and Methods: The study involved 150 students and 10 teachers from five schools, selected to represent diverse educational settings (urban and rural). A mixed-methods approach was employed, combining classroom observations, interviews, focus groups, and surveys. Data were analyzed to assess the frequency and impact of translingual practices on language proficiency, student engagement, inclusivity, and perceived barriers to implementation. Results: Findings indicated that students in classrooms with more frequent translingual practices showed a greater improvement in language proficiency (13.7-point increase vs. 7.3 points in lower usage classes). Students reported feeling more comfortable and confident, with 85%-87% agreeing that using their first language alongside the target language helped their learning. Teachers identified several barriers, including time constraints, concerns about hindering second language acquisition, and lack of bilingual resources. Urban schools showed better outcomes due to greater resources, but rural schools also benefited, highlighting the adaptability of translingual practices. Conclusions: Translingual practices are an effective tool for enhancing language acquisition, fostering inclusivity, and improving student engagement. However, successful implementation requires overcoming barriers such as limited resources, curriculum constraints, and lack of teacher training. With proper support, translingualism can be an inclusive and transformative approach to language education in diverse contexts.